Optimal particle ratio to maximize the dynamic range of Magnetorheological Fluid (MRF) damper for prosthetic limb - Nordin, Norhidayati Diana; Abdul Muthalif, Asan Gani; Saleh, Tanveer; Zainul Azlan, Norsinnira (IEEE, 2015)
Amputation is a process of removing part of the body through surgery. Common reasons for limb amputations include diseases, poor blood circulation to the limb and severe injuries. In order to assist amputees to lead a normal life, prosthetic limb - the artificial device that replaces missing body part, needs to be designed as close as human limb. One way of achieving this is through the implementation of magnetorheological fluid (MRF) damper in human lower limb. The MR fluid, due to its capability of changing its rheological property, is able to provide comfort to the amputees throughout the walking gait cycle, based on its damping characteristic. To design an effective MR fluid damper, one needs to maximize the dynamic range of the damper. This paper presents the simulation of an MRF damper, in order to determine the relationship between the current, fluid mixture viscosity as well as the particle ratio (up to a ratio of 0.55). COMSOL Multiphysics software is used to perform simulation study. By maintaining the number of particles suspended in the fluid, increasing the particle ratio increases the stress. However, the maximum change of stress level, with respect to the applied current is observed at a ratio of 0.51.